An analysis of wage difference between gender in Malaysia using weighted sample - Mahdir Bahar (2022)
The rapid economic development has changed the structure of the labour market especially in terms of composition of employment. Therefore, the development of a country that has been involved in economic change has brought a lot of transformations to the pattern of women's involvement in economic activity. Gender wage difference in labour market prevails all over the world where men tend to earn a wage rate higher than women. This study aims to analyse gender wage differential based on data of The Salaries & Wages Survey 2018 from Department of Statistics Malaysia (DOSM). The objective of this study is to analyse gender wage differences and identify factors of wage determinations between male and female workers in the Malaysian labour market. Three determinants factors are considered, namely demographic factors, human capital aspects and job characteristics. The analysis of the study takes into account the weighted samples from stratified sampling to provide an overview of recipients’ income in Malaysia. The results of non-parametric mean comparison analysis showed that there were significant differences in the mean distribution for each category of variables studied. The results using wage model estimation revealed that demographic factors, human capital aspects and job characteristics play an important role in determining wage differences based on gender. In Malaysia, the salaries and wages of male workers are more dominant in determining the salaries and wages of overall recipients’ income.